Dimensi Profetisme dalam Perjalanan Eksistensial Tokoh Utama pada Novel Seporsi Mie Ayam Sebelum Mati Karya Brian Khrisna - Risqi Kurniasih; Akhmad Fauzan; Onok Yayang Pamungkas; Mulasih Mulasih (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This article aims to uncover the dimension of prophetism in the existential journey of the main character through an interdisciplinary approach between Kuntowijoyo's prophetic literature and Jean-Paul Sartre's existentialism. This research method uses a qualitative hermeneutic method. The data collection technique uses the read, record, and triangulation methods of data to ensure the validity of the data. The data in the study includes narratives, monologues, dialogues presented in the form of words, phrases, and sentences that contain the dimension of prophetism. The source of this research data was taken from a novel entitled A Portion of Chicken Noodles Before Death by Brian Khrisna. The results of the study show that in the existential journey of the main character, there is a prophetic dimension, including humanization, liberation, and transcendence according to Kuntowijoyo's theory. The humanization dimension is depicted by the actions of the characters that reflect the humanizing attitude of humans, such as maintaining brotherhood, helping, and respecting others. The dimension of liberation is shown in the form of liberation of the economic system by efforts to free oneself from poverty, liberation of the knowledge system, and internal liberation in the form of self-acceptance of His destiny. Third, the dimension of transcendence is reflected in the behavior of the character who is khauf, qana'ah, ridha, sincere, tawakkal, raja', gratitude, and aspects of spiritual awareness in the main character. The prophetic dimension plays a role in resurrecting the consciousness and existence of the main character to return to living an authentic life (Sartre). This study confirms that works of popular fiction can be explored for their prophetic values and can be integrated with the philosophy of existentialism as a medium of inner reflection in the face of the complexities of modern life